Characteristics of Regular Pulse Bursts Generated From Lightning Discharges - Yanhui, Wang; Xiangpeng, Fan; Tuo, Wang; Yingchang, Min; Yali, Liu; Guo, Zhao (Frontiers in Environmental Science, 2021)
In this work, we studied the waveforms of all lightning discharges from about 15 min. Eighty-three percent of all lightning discharges contain particular waveforms called regular pulse bursts (RPBs), which have regular microsecond-scale electric or magnetic field pulses. Maximum proportion of RPBs occur in middle or rear of lightning discharges. Prior to or after RPBs, there is always a chaotic pulse period. The analysis indicated that RPBs are caused by a secondary discharge in the fractured old breakdown channel, likeness to dart-stepped leader occuring in negative cloud-to-ground discharge (-CG). Four types of RPBs, namely, category of normal RPBs, category of back RPBs, category of symmetric RPBs, and category of reversal RPBs, were sorted in the light of the evolution of the pulse amplitude, interval between neighboring pulses and pulse polarity. In addition, the difference between normal RPBs and back RPBs was considered to be caused by the distance between neighboring charge pockets and the magnitude of the charge in every charge pocket. The symmetric RPBs were considered to be caused by a discharge channel with a large central charge area. Reversal RPBs were considered to be caused by a bending channel or superposition of two or more RPBs. We located some RPBs in a typical intra-cloud flash (IC) in three-dimensional. The analysis showed that the developing velocity of RPBs ranged from approximately 1.2 × 106 m/s to 3.0 × 106 m/s, which slower less than both of the dart leader or dart-stepped leader process from previous studies. And we found it is several meters to dozens of meters that the lengths range of discharge step which between two adjacent pulses.